On the Relationship of Resilience and Mental Vitality with Addiction Potential among Students - M Ghanbari-Talab; M Fooladchang (Drug Control Headquarters, Research and Education Office, 2015)
Objective: The present study was an attempt to explore the relationship of addiction potential and resilience with mental vitality. Method: This was a descriptive-correlational study. Lordegan Payame Noor University students constituted the population of this study. Then, the number of 172 students was selected as the participants via random sampling and responded to Resilience, Addiction Potential, and Mental Vitality questionnaires. Results: Data analysis indicated that resilience and mental vitality were negatively correlated with addiction potential. Furthermore, the results showed that resilience and mental vitality were predicators of addiction potential. Conclusion: According to the findings of this study, it can be concluded that mental vitality and resilience are one of the factors effective in the generation of potential for substance use in individuals.